PEMBERIAN PERLAKUAN SENSOMOTORIK TERHADAP ANAK STUNTING UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF PADA TINGKAT PENDIDIKAN ANAK USIA DINI - MAYASARI, IKA RILA (MOTORIC, 2024)
This research is a quantitative descriptive study that aims to produce a learning program for stunted children to improve cognitive abilities in stunted children at PAUD age. The learning program used uses a sensoromotor stimulus which is expected to be able to increase the ability of stunted children. This research was tested on six stunting children aged 4 to 6 years. This research was carried out in three meetings. This research was carried out for three months at BKB Harapan Bunda, Randu Pitu Gempol Pasuruan village. Data collection techniques carried out consisted of observation, interviews and documentation. The results of the study show that the development of stunting children's cognitive abilities by providing sensormotor stimuli can be carried out effectively. This is indicated by a moderate n-gain value, which means that there are differences in cognitive abilities before and after treatment. Keywords: Quantitative, Stunted, Kognitive Ability